PENGARUH PENGGUNAAN METODE PEMBIASAAN TERHADAP PEMBENTUKAN KARAKTER DISIPLIN ANAK DI PAUD SARTIKA ASIH KABUPATEN CIAMIS, JAWA BARAT - Ida Nurhayati; Neng Kurniasih; Susi Susanti; Yusuf Hidayat (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Habituation is one of the methods used to form discipline to early childhood. This study aims to determine the influence of using habituation method to form discipline in early childhood aged 5-6 years in PAUD Sartika Asih. The study employs a quantitative method under pre-experimental approach (one group pre-test and post-test design). The findings of the study show that based on the result of the t-test, t-observed = 13.073 > t-table = 2.040, so H0 is rejected and H1 is accepted. Thus, the use of the habituation method is able to effect in informing early childhood’s discipline in PAUD Sartika Asih. In addition, there are other findings in this study, including: the early childhood gets more attention from the parents at home and the teacher at school, because they give the real examples of how to do discipline in daily life; early childhood feels more enthusiastic in starting activities at school, because he/she and his/her parents arrive at school on time; and the early childhood feels proud of his/her parents because they give the model of how to return the toys to its place and how to wait for the turn. In conclusion, the use of habituation method has an effect to form of early childhood’s discipline at PAUD Sartika Asih.